2003
DOI: 10.1113/jphysiol.2002.029454
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in human motor cortex input–output characteristics

Abstract: ProtocolAn input-output curve for the MEP amplitude evoked in the resting FDI by TMS was constructed. Ten TMS were delivered at each intensity, beginning 10-12 % below resting threshold and increasing incrementally in 3 % steps to either 100 % of stimulator output, or to a stimulus intensity where MEP amplitude had Age and sex differences in human motor cortex input-output characteristics Julia B. Pitcher, Kirstin M. Ogston and Timothy S. Miles Department of Physiology, The University of Adelaide, Adelaide, So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
198
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(236 citation statements)
references
References 22 publications
29
198
4
Order By: Relevance
“…This supports an earlier study that found no gender effects on limb MEP magnitude (Pitcher et al 2003). Another study measured MEPs from the upper limb and found no gender effects on MEP magnitude and latency in younger subjects, after correcting the latencies for the subject's arm length (Livingston et al 2010).…”
Section: Discussionsupporting
confidence: 77%
“…This supports an earlier study that found no gender effects on limb MEP magnitude (Pitcher et al 2003). Another study measured MEPs from the upper limb and found no gender effects on MEP magnitude and latency in younger subjects, after correcting the latencies for the subject's arm length (Livingston et al 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies regarding the reliability of TMS measures have provided equivocal results, with some studies demonstrating moderate to good reproducibility for normalized map volume and for map area (Malcolm et al, 2006;, and other studies showing poor to moderate reproducibility for the same measures (Kiers et al, 1993;Mortifee et al, 1994). The trialto-trial variability of MEP amplitude is well known (Kiers et al, 1993;Pitcher et al, 2003;Smith et al, 2011) and could explain these equivocal results. Our data showed poor reliability for map area either at rest or under active condition, but for map volume a better reliability was observed under active condition.…”
Section: Reliability Of Tms Measuresmentioning
confidence: 50%
“…Again, the absence of a significant association between resting and active MEPs for measures obtained at 110% of the MT could reflect the large trial-to-trial variability of MEP amplitude. This variability can be particularly important at lower stimulation intensities (Pitcher et al, 2003). Importantly, the presence of an association for MEP amplitudes obtained at 120% of MT but not for…”
Section: Mep Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies that have reported RMT and AMT in young and elderly subjects have shown no age-related change in these measures (Kossev et al, 2002;Wassermann, 2002;Pitcher et al, 2003;Oliviero et al, 2006;Rogasch et al, 2009;Smith et al, 2009;Cirillo et al, 2010;Smith et al, 2011). However, in all cases there is typically a trend towards increased RMT and AMT in elderly participants.…”
Section: Sici Is Increased In Elderly Participants With Ap Coil Orienmentioning
confidence: 90%